2012
DOI: 10.1371/journal.pone.0051280
|View full text |Cite
|
Sign up to set email alerts
|

Associations of BDNF Genotype and Promoter Methylation with Acute and Long-Term Stroke Outcomes in an East Asian Cohort

Abstract: BackgroundBrain derived neurotrophic factor (BDNF) has been shown to play an important role in poststroke recovery. BDNF secretion is influenced by genetic and epigenetic profiles. This study aimed to investigate whether BDNF val66met polymorphism and promoter methylation status were associated with outcomes at two weeks and one year after stroke.Methods and FindingsA total of 286 patients were evaluated at the time of admission and two weeks after stroke, and 222 (78%) were followed one year later in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 32 publications
5
70
1
1
Order By: Relevance
“…The role of epigenetics in post-stroke recovery has recently come to the fore with exciting findings [2628]. Recent investigation suggests that microRNA (miRNA) play an important role in the molecular response to cerebral ischemia.…”
Section: Neuroplastic Changes Following Strokementioning
confidence: 99%
“…The role of epigenetics in post-stroke recovery has recently come to the fore with exciting findings [2628]. Recent investigation suggests that microRNA (miRNA) play an important role in the molecular response to cerebral ischemia.…”
Section: Neuroplastic Changes Following Strokementioning
confidence: 99%
“…This polymorphism has been shown to partially affect activity-dependent BDNF secretion by reducing BDNF secretion by 30% in Met/Met neurons in-vitro [90] and to impair motor skill acquisition in-vivo [78,79]. In patients with ischemic stroke, the Val66Met allele was associated with poor outcomes and physical disability after stroke, and with slower motor recovery [83,9193]. Analysis of pathophysiological difference between Val and Met patients suggests that both can retain the ability to recovery after stroke; however, the rate and trajectory of recovery appears to be difference [94].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Until now, few studies have focused on the genetics of initial neurological deficit, although studies at 2 and 4 weeks post stroke have reported an association between brain-derived neurotrophic factor (BDNF) and outcome. 33,34 Large efforts on studying genetic impact on early treatment effects of thrombolysis are underway. 40 Longer term prognosis on neurological/physical deficit can be grouped into neurological outcomes, stroke recurrence, and mortality.…”
Section: Neurological/physical Deficitmentioning
confidence: 99%